Food-Borne Endocrine-Disruption: An EU Risk Governance Perspective - Maria El Gemayel (European Journal of Risk Regulation)
Exposure to endocrine disrupting chemicals is linked to negative health impacts, including non-communicable diseases such as obesity, cardiovascular diseases and cancer. This disease burden compromises consumer safety and costs the European Union an estimated €163 billion per year. Given these stakes, the importance of effectively regulating EDCs in food is paramount. Yet regulators face difficult challenges: scientific uncertainty, the ubiquity of EDCs in food products, and pressure from economic and political interests all complicate legislative responses. From a risk regulation perspective, the core problem is how to protect public health from EDC risks in food amidst these uncertainties and constraints. This paper addresses the problem by examining the current EU regulatory framework for managing EDCs in the food supply chain, identifying gaps and weaknesses, and proposing improvements to better safeguard public health. From this risk regulation perspective, the paper highlights the benefits of ensuring regulatory action keeps pace with scientific evidence, leveraging the General Food Law Regulation for a comprehensive approach to EDCs, and developing sector-specific EDC regulation across the food supply chain.